IGBO TRADITIONAL MEDICINE AND HEALING - Anyanwu, Herbert Onyema (Journal of Dharma, 1999)
Among .the Igbo life is usually regarded as the most precious gift of the Supreme Being and as such it must by protected and prolonged as much as possible. Whenever there is any threat to life by disease and other misfortunes, steps are taken to eliminate the source of danger and get total security. Igbo cosmology is world affirming and thus demands that life in the world must be kept free from problems especially ill-health and obstacles which may hinder the fulfilment of the desired goals. The Igbo attach high value to life, anything that tampers with it is rejected but "any practice or institution that promotes or prolongs life and helps to make it more abundant is encouraged.